Associations between self-reported obstetric complications and experience of care: a secondary analysis of survey data from Ghana, Kenya, and India - Ntemena Kapula; Emma Sacks; Dee T. Wang; Osamuedeme Odiase; Jennifer Requejo; Patience A. Afulani; the Revisioning EmONC Quality of Care Workgroup (BMC, 2023)
Plain language summary In several studies and reports, women have described mistreatment by health providers during childbirth in health facilities. Particularly in low- and middle-income countries, such mistreatment has negative effects on women's decisions to seek maternity care in health facilities. It is unclear if women with complications are more or less likely to experience some forms of mistreatment compared to women without complications. In this study, we examined 31 experience of care indicators in three domains: (1) Supportive Care; (2) Respect and Dignity; and (3) Communication and Autonomy from the validated Person-Centered Maternity Care (PCMC) questionnaire. We compare these experience of care indicators between women who report obstetric complications and those who don't report complications, by the reported severity of the complications, and by their mode of delivery. The study included data from three countries: Ghana, Kenya, and India. The results showed that the experience of care among women who reported obstetric complications was not consistently better or worse than that of those who did not have complications. Therefore, efforts should be made to improve the experience of care in health facilities for every birthing woman. Additionally, women who delivered via c-section had consistently better experiences than women who delivered vaginally. More studies are needed to understand the relationship between mode of delivery and women's experience of care.